Strategi Sekolah Dalam Meningkatkan Mutu Lulusan: Usaha Sekolah Bertahan Dalam Persaingan - Rabial Kanada; Febriyanti Febriyanti (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This study reviews strategies related to improving the quality of graduates at SMAN 1 Semende Darat Laut. The purpose of this research is to find out the strategies for improving the quality of graduates from public senior high schools in South Sumatra and the supporting and inhibiting factors in improving the quality of graduates. In this study, the type of research used was qualitative research in which the main source of informants was the school principal. The supporting informants were the deputy heads of student affairs and teachers. The data obtained by the method of observation, interviews, and documentation. While the data analysis technique used is data reduction, data presentation and drawing conclusions. The results of this study indicate that the strategy to improve the quality of public high school graduates in South Sumatra has been going quite well. This can be seen from the strategy implemented, namely an increase in teacher competence, additional learning programs, improvement of sarpas, and extracurricular development. The supporting factors include: establishing good communication between leaders and subordinates, motivation to support continuing education, teachers are all undergraduates, while the inhibiting factors are lack of funds, lack of facilities and infrastructure to support graduation programs, and lack of time in extracurricular activities.